Nurses' adaptation instrument in the oncology wards: Development and psychometric testing - Shahrzad Ghiyasvandian; Hooman Shahsavari; Azam Ghorbani; Masoumeh Zakerimoghadam; Pegah Matourypour; Golnar Ghane (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Understanding adaptation is strongly influenced by the culture and beliefs of every society. By increasing knowledge about the different dimensions which require the adaptation in different aspects requiring the nurse adaptation in oncology, a clear definition of the problem can be stated. Because of the lack of a standard and appropriate tool for the culture of the Iranian society, this aimed at developing and validating the nurse adaptation tool in the oncology departments. METHODS: This research is a methodological study and an exploratory mixed method being conducted in three main steps of conceptualization, production of items, and field test. Inductive conceptualization was performed through qualitative methodology and conventional content analysis approach; in the second step, developed instrument was evaluated in terms of face validity, content validity, and construct validity. In the third step, sampling of oncology nurses was done and exploratory factor analysis was performed for evaluating the construct validity, adequacy of sampling, and dimensioning. Cronbach's alpha was calculated for checking the reliability of the instrument. RESULTS: The oncology nurse adaptation questionnaire was formed with twenty items in four main dimensions, including "emotional factors," "supportive factors," "work-related factors in the ward," and "factors related to job conditions." The reliability of the tool was confirmed by evaluating the internal consistency with Cronbach's alpha, which was above 0.7 for each dimension and 0.82 for the whole instrument. CONCLUSION: This instrument can be used as a practical tool for determining the adaptation of oncology nurses for providing evidence to improve the work conditions of nurses by improving the working conditions in the workplace and providing facilities with individual intervention, and the outcome will be care of patients with high quality.